Resistance of Six Lines from Farmers against Bacterial Leaf Blight (Xanthomonas oryzae pv. oryzae) - Suryaningsih, Andika Septiana; Triwidodo, Hermanu; Wiyono, Suryo (Jurnal Fitopatologi Indonesia, 2023)
Resistance of Six Lines from Farmers against Bacterial Leaf Blight (Xanthomonas oryzae pv. oryzae) Bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae is a disease that detrimental to rice production in Indonesia. One effort to control the disease is to use BLB resistant varieties. This study aims to evaluate the development of bacterial leaf blight on six lines (TCIPB202101, TCIPB202102, TCIPB202103, TCIPB202104, TCIPB202105, and TCIPB202106) and two control varieties (Ciherang and Inpari 30). Green house experiment was conducted in Cikabayan Dramaga using artificial inoculation. The study was conducted by observing the incubation period, lesion length and disease intensity at 7 and 14 days after inoculation (DAI). The results showed that all the lines tested were resistant to BLB and had better resistance compared to the control varieties. The TCIPB202105 and TCIPB202106 lines had the best resistance response with an average disease intensity below 1%. Meanwhile, the TCIPB202101 and TCIPB202102 lines had the highest percentage of disease intensity although they are still considered as moderately resistant category.